Traffic Engineering At The Kim Ii Roundabout - Amrizal, Amrizal; Juni S Br Tarigan, Pagit; Pramono, Egi (Publisher Cv. Inara, 2024)
As the manager of the industrial area, currently PT. KIM has problems related to traffic jams that occur around the KIM roundabout and to reduce the number of traffic accidents at KIM due to collisions between vehicles from opposite directions, it is necessary to carry out traffic engineering in the area. Traffic engineering is related to the implementation of repair work Roundabouts are not only road construction improvements but also include traffic engineering before, during and after construction. Simulation of traffic conditions to provide alternative solutions to traffic problems that occur at the KIM II Roundabout using VISSIM software. From the results of the simulations that have been carried out, it can be seen that almost all road sections have a level of service F, which means they have a VCR value > 1. This is included in the oversaturated category, side obstacles and delays increase, stopping and moving events increase, if the flow increases, the vehicle speed is equal to zero (complete stop). This condition causes delays on one of the sections of 151 vehicle seconds and this condition is not very good because it will lengthen the queue of vehicles crossing the roundabout. In accordance with the simulation that has been carried out, and based on several applicable regulations regarding the traffic system at roundabouts, several alternatives for handling traffic problems in the KIM II Roundabout area are provided.